Cigarette smoking and risk of primary systemic vasculitis: a propensity score matching analysis - Khabbazi, Alireza; Alinejati, Babak; Hajialilo, Mehrzad; Ghojazadeh, Morteza; Malek Mahdavi, Aida (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Introduction: Considering limited data about the association between smoking and primary systemic vasculitides (PSV), present study aims to investigate smoking habit in PSV patients compared to healthy subjects as well as to examine the effect of smoking on clinical characteristics, disease activity and disease outcome in PSV patients. Methodology: We included 126 patients diagnosed with PSV and 210 age- and sex-matched healthy controls. Demographic and clinical information and smoking history of patients and healthy controls were obtained by direct interview and questionnaire. Individuals who had smoked at least 100 cigarettes in their lifetime before the first symptom of vasculitis were classified as smokers; those who had never smoked or smoked less than 100 cigarettes in their lifetime were categorized as never smokers. Disease activity was evaluated by Birmingham Vasculitis Activity Score (BVAS). Disease outcome was assessed by vasculitis damage index (VDI) and the number of patients with disease in remission. Propensity score matching analyses (PSM) for reducing the heterogeneity between studied groups and calculating the actual effect of smoking in PSV was performed. Results: No significant differences were observed in clinical manifestations and disease outcome of patients including VDI and the patients with disease in remission between ever and never smokers. However, disease activity according to BVAS in ever smokers was significantly higher than never smokers (P=0.020). PSM resulted in 82 patients with PSV, and 164 matched healthy persons with similar baseline characteristics. By multivariate logistic regression and after adjustment for age, sex, marital status and educational status, ever smoking was not significantly associated with an increased risk of PSV compared with never smoking. Discussion and conclusion: Our study indicated a significant association between disease activity and smoking as well as a non-significant association between the clinical manifestations and disease outcome of PSV with smoking in Azeri population. Although further studies are needed to confirm these preliminary results, it seems that smoking may not be a significant risk factor for PSV.